YAC/P1 contigs defining the location of 56 microsatellite markers and several genes across a 3.4-cM interval on mouse Chromosome 11 - Nehls, Michael; Lüno, K.; Schorpp-Kistner, Marina; Pfeifer, D.; Krause, S.; Matysiak-Scholze, U.; Dierbach, H.; Boehm, Thomas (Mammalian genome, 1995)
The characterization of three YAC/P1 contigs from adjacent segments of the central region of mouse Chromosome (Chr) 11 is described. These contigs are based upon 63 YACs and 40 P1 recombinants. From these clones, 185 end sequences were obtained, of which 147 sequences could be converted into sequencetagged sites and mapped within the three contigs. Deletions were detected in 16 out of 63 YACs; 19 of 63 YACs were found to be chimeric. No such aberrations were found in P1 recombinants. A total of 22 public and 34 newly developed microsatellite markers were unambiguously localized to and ordered in the contigs. In the cryb1/Nf1 interval of the central contig, several new genes have been identified by exon trapping and precisely localized with respect to known STS markers.
Gesehen am 24.04.2024